Deep learning and natural language processing in computation for offensive language detection in online social networks by feature selection and ensemble classification techniques - Anand, M.; Sahay, Kishan Bhushan; Ahmed, Mohammed Altaf; Sultan, Daniyar; Chandan, Radha Raman; Singh, Bharat (Theoretical computer science, 2023)
Offensive communications have made their way into social media posts. Using computational algorithms to distinguish objectionable content is one of the most effective ways to deal with this problem. One of the most effective approaches to deal with this issue is to use computational methods to distinguish undesirable content. This research aims to tackle MOLD_DL (Multilingual Offensive Language Detection using deep learning) techniques and natural language processing used in feature selection and classification. Here the dataset has been collected from YouTube, Twitter and Facebook, which has been pre-processed for noise removal, filtering and removing the stop words and segmented. The feature selection has been carried out for segmented data using Fuzzy based convolutional neural network (FCNN). Then the extraction of selected features and classification has been carried out using ensemble architecture of Bi-LSTM model with Naïve Bayes architecture hybrid with Support Vector Machines (SVM). Evaluation of offensive language detection is classified automatically based on the emotions of the text. Here the experimental analysis has been carried out for YouTube, Twitter and Facebook datasets in terms of accuracy of 98%, precision of 95%, recall of 90%, F-1 score of 92.5% and RMSE of 45% with the confusion matrix in detecting offensive text of various languages. •Offensive communications have made their way into social media posts.•This research aims to tackle MOLD_DL (Multilingual Offensive Language Detection using deep learning) techniques and natural language processing used in feature selection and classification.•Here the dataset has been collected from Social Networks.•Finally, these extracted features have been classified using ensemble architecture of Bi-LSTM model with Support Vector Machines (SVM) which is hybrid with Naïve Bayes architecture.